Aufgaben als Lerngelegenheiten für konzeptuelles und prozedurales Wissen zu Brüchen – Eine vergleichende Schulbuchanalyse (mathematica didactica, 2019)
When learning fractions, students are expected to develop conceptual knowledge as well as procedural knowledge. In a comparative analysis of five textbooks we thus examined the chapters on fraction operations with a focus on the ways in which both knowledge types were addressed. Moreover, we investigated which role visualizations play in corresponding learning opportunities. A quantitative content analysis revealed that after a visualization-based introduction focusing on both knowledge types, the following tasks focused predominantly on procedural knowledge whereas the use of visualizations did not live up to the state of the art in mathematics education.